Attainable Range Prediction of Group Product by Aggregation of Individual Products in Group Learning with Kit-build Concept Map (International Conference on Computers in Education, 2020)
Recently, we can collect and analyze a variety of data in learning with the development of information and communication technology and also expect that the prediction of learning with the data enables a deep reflection for enhancing the learning experience. This paper describes a method for the attainable rage prediction of the group learning products from aggregation of an individual's concept map with the Kit-build (KB) approach. To test this method, we examined the prediction results from the data collected from a classroom lesson. The results show that most of the actual results are in good agreement with the prediction, and the comparison between the actual results and the predictions could be useful for the teacher.